2016
DOI: 10.1002/ece3.2405
|View full text |Cite
|
Sign up to set email alerts
|

Moving south: effects of water temperatures on the larval development of invasive cane toads (Rhinella marina) in cool‐temperate Australia

Abstract: The distributional limits of many ectothermic species are set by thermal tolerances of early‐developmental stages in the life history; embryos and larvae often are less able to buffer environmental variation than are conspecific adults. In pond‐breeding amphibians, for example, cold water may constrain viability of eggs and larvae, even if adults can find suitable thermal conditions in terrestrial niches. Invasive species provide robust model systems for exploring these questions, because we can quantify therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 87 publications
(112 reference statements)
1
7
0
Order By: Relevance
“…Differences in mean temperature can have strong effects on development time, growth rate, and body mass in ectotherms (Ratte, 1985;Atkinson, 1994;Kingsolver et al, 2009;Williams et al, 2012). However, independent of differences in mean temperature, we found that variation in temperature experienced during development also tends to decrease the developmental time and increase the growth rates, and body mass ( Figure 3A-C), consistent with other invertebrates (Ratte, 1985;Atkinson, 1994;Kingsolver et al, 2009;but see Kjaersgaard et al, 2013) as well as vertebrates (Wijethunga et al, 2016;Pepin, 1991;Shine & Harlow, 1996;Booth, 1998). Thus, ectotherms typically benefit from experiencing variable temperatures during their life-histories, as long as the rearing temperatures are within physiological limits (Worner 1992;Shine & Harlow, 1996;Elphick & Shine, 1998;Angilletta, 2009;Fischer et al, 2011;Colinet et al, 2015).…”
Section: Chapter 5: Discussionsupporting
confidence: 88%
“…Differences in mean temperature can have strong effects on development time, growth rate, and body mass in ectotherms (Ratte, 1985;Atkinson, 1994;Kingsolver et al, 2009;Williams et al, 2012). However, independent of differences in mean temperature, we found that variation in temperature experienced during development also tends to decrease the developmental time and increase the growth rates, and body mass ( Figure 3A-C), consistent with other invertebrates (Ratte, 1985;Atkinson, 1994;Kingsolver et al, 2009;but see Kjaersgaard et al, 2013) as well as vertebrates (Wijethunga et al, 2016;Pepin, 1991;Shine & Harlow, 1996;Booth, 1998). Thus, ectotherms typically benefit from experiencing variable temperatures during their life-histories, as long as the rearing temperatures are within physiological limits (Worner 1992;Shine & Harlow, 1996;Elphick & Shine, 1998;Angilletta, 2009;Fischer et al, 2011;Colinet et al, 2015).…”
Section: Chapter 5: Discussionsupporting
confidence: 88%
“…Such eurythermy may enable the cane toad to breed successfully in a wide range of conditions, and selection to enhance viability at low temperatures accordingly may be weak. Rearing temperature significantly affected many life-history traits, as previously reported by Wijethunga et al [ 6 ], but we lack field data to assess the fitness consequences of variation in traits such as larval duration and size at metamorphosis.…”
Section: Discussionmentioning
confidence: 85%
“…Although previous work has reported rapid adaptation and behavioural adjustments of cane toads in response to selective forces within tropical and arid environments [ 31 , 32 , 36 , 39 ] and shifts in thermal minimum tolerances in adult toads encountering cool conditions [ 10 , 11 ], we saw no such shifts in life-history traits of the early life-stages of toads in response to water temperature. Although toads in southern Australia are exposed to waterbodies that are substantially cooler than those used for spawning in tropical Australia [ 6 , 40 ] or the toads’ native range [ 41 ], the thermal responses of eggs and tadpoles were very similar in tropical versus temperate-zone populations. In an analogous result, Volpe [ 42 ] found no difference in response to experimental temperature of Incilius ( Bufo ) valliceps embryos from thermally diverse breeding environments (early and late breeding seasons).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations